2020
DOI: 10.3390/ijms21249549
|View full text |Cite
|
Sign up to set email alerts
|

In Silico/In Vitro Hit-to-Lead Methodology Yields SMYD3 Inhibitor That Eliminates Unrestrained Proliferation of Breast Carcinoma Cells

Abstract: SMYD3 is a lysine methyltransferase that regulates the expression of over 80 genes and is required for the uncontrolled proliferation of most breast, colorectal, and hepatocellular carcinomas. The elimination of SMYD3 restores normal expression patterns of these genes and halts aberrant cell proliferation, making it a promising target for small molecule inhibition. In this study, we sought to establish a proof of concept for our in silico/in vitro hit-to-lead enzyme inhibitor development platform and to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…The overall goal of this study was to determine the relative efficacy of NO, delivered by GSNO only (Group 1), and the combination therapeutic, SMYD-3 inhibitor (inhibitor-4) and NO from GSNO (Group 2) on human breast carcinomas MCF7 and MDA-MB-231. The impact of inhibitor-4 alone was assessed in a separate study conducted by our collaborators, Alshiraihi et al [29]. Various methods were used to determine efficacy, including cell viability assays (MTT and CTB), colony formation assays, LIVE/DEAD cytotoxicity assays, and cell apoptosis assays (Caspase-Glo 3/7 and Annexin V/PI).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall goal of this study was to determine the relative efficacy of NO, delivered by GSNO only (Group 1), and the combination therapeutic, SMYD-3 inhibitor (inhibitor-4) and NO from GSNO (Group 2) on human breast carcinomas MCF7 and MDA-MB-231. The impact of inhibitor-4 alone was assessed in a separate study conducted by our collaborators, Alshiraihi et al [29]. Various methods were used to determine efficacy, including cell viability assays (MTT and CTB), colony formation assays, LIVE/DEAD cytotoxicity assays, and cell apoptosis assays (Caspase-Glo 3/7 and Annexin V/PI).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, the RSNO, GSNO, was shown to exhibit tumoricidal characteristics [30][31][32]. Likewise, a separate study indicated that a SYMD3 inhibitor, inhibitor-4, demonstrated potent impacts on two breast cancer lines, MCF7 and MDA-MB-231 (both lines linked to overexpression of SMYD3) [29]. By combining the two for a combination therapeutic, GSNO and inhibitor-4, we sought to surpass the efficacy of each individual therapeutic on MCF7 and MDA-MB-231 breast cancer lines.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, the existing drug Diperodon has been reported as a new allosteric ligand interacting with SMYD3 and represents a good starting point for the design of compounds acting as modulators of noncatalytic SMYD3 functions [30]. In addition to these, recent studies identified new selective SMYD3is (e.g., BAY-6530, covalent inhibitors 1-4) [26,31], thereby contributing to the ongoing efforts to develop effective SMYD3is that might be used as anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%